The human enhancement debate and disability : new bodies for a better life - Eilers, Miriam; Grüber, Katrin; Rehmann-Sutter, Christoph, 1959- (Palgrave Macmillan, 2014)
How does the idea of enhancement relate to disability? At first glance, it might seem simple: enhancement is gain, disability is loss of function, but a closer looks reveals a rich and complex relationship, where the disability perspectives offers an invaluable insight in unpicking the controversy surrounding the social and ethical implications of improving the human condition. While rejecting a dualistic divide between 'therapy' and 'enhancement', enhancement bioethics can benefit from the study of interdisciplinary disability studies by placing the question of a 'better life' for those who might become enhanced on experiential ground; in preventing bioethics from relying on reductionist biomedical models of functional upgrade; in considering ambivalence in and the side effects of improvements; and in making bioethics more alert to possible discriminatory implications.